RÅDSMØTET SOM EVENT LOKALE PROGRESJONS- OG TILBAKEFØRINGSPRAKSISER I ET NORSK HØYSIKKERHETSFENGSEL INSPIRERT AV ET DELEUZIANSK BLIKK - Fransson, Elisabeth (Psyke & Logos, 2015)
The council meetings in prisons is an old and well-established institution in Norway, where employees considering inmate applications for leave of absence, transfer to lower security and release on probation of 2/3 part time. The council members are bound by legislation, regulations and guidelines, but they also manage prison professional judgment. In the article we ask what kind of knowledge about local progression, progression and reversal practices, practices that can be produced, by reading councils inspired by a Deleuzian view? Based on critical ethnography, we have studied the council meetings on the basis of a Deleuze discussion about what a body can do. The article shows how council members, through what is done and said, moves the prisoner application forward to a vote that either endorses or discourages the application. The article clarifies council participants’ categorizations of inmates and shows how time and trust are woven into local progression- and reversal practices. Further on, how meaningful categories, such as trust, time and the process of becoming, in various ways, are woven into local progression- and reversal practices. Dilemmas council members are facing are highlighted, and the article raises questions relating to the council meeting’s safeguarding of the inmates right to predictability and equal treatment.